2019
DOI: 10.1002/2050-7038.12321
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic response enhancement of grid‐tied ac microgrid using salp swarm optimization algorithm

Abstract: Summary To alleviate the overloads in the power system and to reduce the exponential growth in carbon dioxide (CO2) emissions, deployment of the renewable energy sources (RES) into the power system is the need of the hour. However, injecting these RES into the current power system network causes large voltage and power overshoots hence deteriorate the transient response and power quality of the overall power system. In this paper, an efficient solution of the above‐mentioned issues is explored by developing an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 29 publications
0
27
0
Order By: Relevance
“…28 The EVIR controls the voltage/current using power electronic devices; they are an actuator, exciter, generator, and sensor. 29 If we denote the rated voltage, rated current, measured voltage, output voltage, and output current of an EVIR system by…”
Section: Compensator Tuningmentioning
confidence: 99%
See 1 more Smart Citation
“…28 The EVIR controls the voltage/current using power electronic devices; they are an actuator, exciter, generator, and sensor. 29 If we denote the rated voltage, rated current, measured voltage, output voltage, and output current of an EVIR system by…”
Section: Compensator Tuningmentioning
confidence: 99%
“…21 Hence, the proposed EVIR regulator assures to keep the system stable even in the presence of large parameter variations. 22,29…”
Section: Robustnessmentioning
confidence: 99%
“…Evidently, [28] showed that a better damped and transient performance is achieved using GWO. The quality improvement of PI parameter for the grid-connected PV system was discussed in [29,30]. The accuracy, reliability, and efficiency of both frequency and voltage were improved with minimal harmonic distortion using SSA.…”
Section: Introductionmentioning
confidence: 99%
“…To the level of the information available to the authors, MRFO has not been applied before to solve any optimization issues in renewable energy. Moreover, the fitness function solution of the MRFO approach developed over the employed algorithms in [32] and [29] motivates the authors to utilize this type of bioinspired optimization algorithm. The algorithm process depicts foraging characteristics of Manta rays, namely, the chain, cyclone, and summersault techniques, to develop a proficient optimization standard for solving unusual optimization problems.…”
Section: Introductionmentioning
confidence: 99%
“…Integration of renewable energy resources into power grid, 1,2 has led to the microgrid development for more accurate regulation of both AC and DC state variables 3‐5 . Among microgrid configurations, the hybrid DC/AC microgrid has attracted high attentions from prospective control system design in recent years 6‐9 . Reference 10 has proposed a straightforward and effective strategy to solve the problem regarding the power injections of hybrid AC/DC microgrids.…”
Section: Introductionmentioning
confidence: 99%